МОДЕЛЮВАННЯ ВЗАЄМОДІЇ В РОЗПОДІЛЕНИХ ІНТЕЛЕКТУАЛЬНИХ ІНФОРМАЦІЙНИХ СИСТЕМАХ МЕТОДАМИ АВТОМАТИЧНОГО ПЛАНУВАННЯ - KHORKANIN, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This paper delves into the intricacies of resource management and task scheduling within distributed information systems, aiming to propose a processing flow for effective coordination and information exchange among system components. The research focuses on the coordination of actions and information exchange within distributed intelligent systems, highlighting the issues stemming from asynchronous operations, resource management complexities, and the necessity to adapt to dynamic environmental conditions. By leveraging these challenges, the study presents results showcasing the impact on task execution delays, suboptimal resource utilization, and overall system performance degradation. Through experimentation, it underscores the complexity inherent in coordinating distributed intelligent systems and emphasizes the need for an efficient synchronization mechanism. The proposed approach aims to mitigate these challenges, offering insights into modeling, automatic planning, and optimization within information systems. Context. The paper focuses on addressing the challenges associated with resource management and task scheduling in distributed information systems. Objective. The purpose of the work is to propose the processing flow for coordination and information exchange between different components of distributed intelligent systems. Methods. The paper presents the research results about coordination of actions and information exchange between components of distributed intelligent systems. These problems can lead to delays in the execution of tasks, inefficient use of resources, and a general decrease in system performance. These difficulties are caused by a variety of factors, including the asynchronous operation of components, the complexity of resource management, and the need to adapt to changing environmental conditions. In current research, we utilized the asynchronous operation of components, the complexity of resource management, and the need to adapt to changing environmental conditions. Results. The paper presents the research results about coordination of actions and information exchange between components of distributed intelligent systems. Conclusions. The experiments confirmed the complexity of coordination and information exchange between these components, which can lead to delays in the execution of tasks, under-optimized use of resources and a general deterioration in system performance. This research was aimed at developing an effective way to sync and coordinate distributed intelligent information systems, including the asynchronous operation of components, the complexity of resource management, and the need to adapt to changing environmental conditions